Characteristics of ecological preferences of ants (Hymenoptera, Formicidae) based on vegetation data - Stukalyuk, S.; Goncharenko, I.; Zhyhalenko , O.; Kozyr, M. (Publishing House "Akademperiodyka" of the National Academy of Sciences of Ukraine, 2025)
This study aimed to identify ecological niches of ant species based on vegetation analysis and to assess their adaptation to environmental conditions using phytoindicative methods. Fieldwork was carried out in 2021 in Chernihiv Oblast, Ukraine, across a range of habitats from natural forests and meadows to agrocenoses and disturbed environments. The analysis revealed marked differences in the ecological preferences and amplitudes of ant species. Lasius niger and Formica cinerea demonstrated the broadest ecological tolerance, particularly to habitat naturalness, humidity, temperature, and soil parameters, indicating high ecological plasticity and adaptability to both natural and anthropogenic environments. In contrast, Formica rufa exhibited a narrower niche, associated mainly with forested habitats and more stable microclimatic conditions. Species such as Myrmica rubra, Tetramorium caespitum, and Formica fusca showed moderate plasticity, with varying responses to nitrogen, salinity, and soil acidity. Some species, including Formica exsecta and Leptothorax muscorum, appeared highly specialized, although limited records constrained interpretation. Phytoindication proved effective for assessing the ecological niches of ants by linking their distribution to vegetation-based environmental gradients. This approach allowed the identification of species with broad versus narrow environmental tolerances and provided insights into their adaptive strategies in heterogeneous landscapes. The findings enhance our understanding of how ant communities respond to environmental variability and demonstrate the value of phytoindication for ecological studies and biodiversity monitoring in changing ecosystems.